Fabrication and characterization of hybrid oil palm /kenaf core fiber-reinforced poly(lactic acid) biocomposites - Umar, Abubakar Birnin-Yauri (2017)
Conventional fiberboards uses wood fiber and carcinogenic urea formaldehyde, and hence poses economic and environmental problems such as deforestation, desertification, reduced biodiversity and emission of toxic formaldehyde. A potentially promising alternative involves the use of natural fibers thermoplastic composites. This study demonstrated the development of hybrid oil palm-kenaf core fiber reinforced poly(lactic acid) biocomposites for use as a clean and sustainable option to the wood fiber board. The kenaf core fiber, as secondary fiber was incorporated into empty fruit bunch fiber, or oil palm mesocarp fiber, melt-blended with PLA and hot-pressed into their corresponding hybrid biocomposites, aimed at achieving synergism. The test results showed the best hybridization performances at 5 wt.% kenaf core fiber into 55 wt.% empty fruit bunch fiber or oil palm mesocarp fiber, and 40 wt.% PLA matrix, corresponding to the 60:40 total fiber to PLA loadings, respectively. Though, the difference in the mechanical and physical properties of the hybrid biocomposites is not large, also they revealed morphological defects and high densities, resulting from high contents of hemicellulose and impurities in the natural fibers. Borax modification of the natural fibers, with a water-washing procedures enhances the material performances of the hybrid biocomposites. The borax treatment caused considerable increase in cellulose compositions, minimal removal of lignin, and significant elimination of hemicellulose and waxy substances, as confirmed through chemical analysis, bulk density, Fourier transform infrared spectroscopy, X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy of the natural fibers. Optimal improvements in the mechanical and physical properties of hybrid biocomposites were observed at 5 wt.% borax concentration. However, the borax-treated hybrid biocomposites revealed few morphological cracks, recorded relatively higher densities, and statistical insignificance of some mechanical properties, which were attributed to brittleness of the PLA. The use of maleic anhydride-modified PLA greatly aided to overcome these anomalies. The borax-treated hybrid fiber reinforced maleic anhydride-modified PLA biocomposites provided the best results. Best hybrids showed impressive performances in other fibre board related properties, though, they recorded densities within the range of high density fiber board. This work revealed that the natural fiber hybridization could offer possible synergism, complement material properties of kenaf core fiber, and provides sustainable application of the oil palm fibers in fabrication of natural fiber based biocomposites.